KUALITAS PELAYANAN ANTENATAL CARE DI PUSKESMAS KOTA JAMBI TAHUN 2010 - , Suryani; , dr. Lutfan Lazuardi, M.Kes., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Based on the annual report the City Health Office of Jambi, the range of K1 and K4 from 2007-2009 has increased. Although likely to increase, but still many patients who expressed dissatisfaction with MCH services at health centers. This can be seen from the preliminary survey by Fitriani (2009) conducted at the PHC Paal V city of Jambi show there are still pregnant mothers are not satisfied with antenatal care. The low satisfaction of pregnant women is probably due to the quality of antenatal care is not up to standard. Objective: To determine the quality of antenatal care at community health centers Jambi City Methods: This study is a descriptive qualitative case study design. Location of the study in 6 health centers city of Jambi. The subjects consisted of pregnant women who visit health centers, midwives in performing services, other sources used as research subjects is the Head of PHC, MCH Kasie DHO Jambi Jambi Municipality and Chairman of IBI. The research instrument in the form of questionnaires, interview guides, observation guidelines and checklist. Analysis of descriptive data (domain analysis) Results: The results showed some midwives providing antenatal care to pregnant women has not been standardized, minimum facilities needed by midwives in providing services already available and complete, some pregnant women have a good perception of aspects of emphaty and some still have a poor perception of aspects of assurance as well as some of the pregnant women who received antenatal care at community health centers is still not satisfied with antenatal care. Conclusion: The quality of antenatal services in health centers Jambi City is still low so that antenatal care provided by midwives has not been going well. For that we need to improve the quality of antenatal care in pregnant women with a way to do satisfaction surveys of pregnant women in order to improve customer satisfaction.